2017
DOI: 10.1177/0748233717703892
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent chromium induces reactive oxygen species and impairs the antioxidant power of human erythrocytes and lymphocytes: Decreased metal reducing and free radical quenching ability of the cells

Abstract: The toxicity of hexavalent chromium [Cr(VI)] in biological systems is thought to be closely associated with the generation of free radicals and reactive oxygen species. These species are produced when Cr(VI) is reduced to its trivalent form in the cell. This process results in oxidative stress due to an imbalance between the detoxifying ability of the cell and the production of free radicals. We have studied the effect of potassium dichromate (KCrO), a [Cr(VI)] compound, on the antioxidant power of human eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 77 publications
(84 reference statements)
1
11
0
1
Order By: Relevance
“…The production of free radicals and ROS is one commonly proposed toxicological mechanism of toxic compounds. Cr(VI) is reduced to its trivalent form in the cells, and most studies indicate that free radicals and ROS that are produced in this process result in cell damage and the inflammatory response [32,33,34]. In our study, an elevated level of ROS was observed when HaCaT cells were treated with Cr(VI) (45 μM) at 30, 60, and 90 min.…”
Section: Resultssupporting
confidence: 52%
“…The production of free radicals and ROS is one commonly proposed toxicological mechanism of toxic compounds. Cr(VI) is reduced to its trivalent form in the cells, and most studies indicate that free radicals and ROS that are produced in this process result in cell damage and the inflammatory response [32,33,34]. In our study, an elevated level of ROS was observed when HaCaT cells were treated with Cr(VI) (45 μM) at 30, 60, and 90 min.…”
Section: Resultssupporting
confidence: 52%
“…Cd binds sulfhydryl groups of proteins and glutathione (GSH) and especially GSH depletion results in increased production of reactive oxygen species (ROS) such as hydrogen peroxide, superoxide anion and hydroxyl radical [39-42]. Cr in contrast enters the redox cycle and acts as a catalyst of the Fenton reaction involving H 2 O 2 , leading to an increase in ROS production and alters erythrocyte membrane fluidity and integrity making erythrocytes more fragile and less osmotic resistant [40, 43]. Gao et al observed following exposure of erythrocytes to increasing concentration of betulinic acid, erythrocyte morphology changed from normal, to a mixture of normal, early discocyte-echinocytes (biconcave disk to star-shape), discocyte-stomatocytes (biconcave disk to cup-shape), echinocytes, echinocytes with vesicles, spherocytes and a few stomatocytes [44].…”
Section: Discussionmentioning
confidence: 99%
“…В процессе восстановления Cr 6+ до Cr 3+ могут образовываться промежуточные неустойчивые степени окисления, которые вызывают образование гидроксильных радикалов. Генерация активных форм кислорода в процессе одноэлектронного восстановления, возможно, происходит при взаимодействии интермедиатов с перекисью водорода по реакциям Хабера -Вейса и Фентона [3,6,13]. Образующиеся при воздействии хрома эндоперекиси обеспечивают повреждение различных макромолекул, структурных компонентов мембран и, как следствие, повреждение тканей и органов, включая печень, почки, элементы крови [5,15].…”
Section: экспериментальная медицинаunclassified